Sugar metabolism and accumulation in the fruit of transgenic apple trees with decreased sorbitol synthesis. Issue 1 (December 2018) - Li, Mingjun; Li, Pengmin; Ma, Fengwang; Dandekar, Abhaya; Cheng, Lailiang
Abstract Both sorbitol and sucrose are synthesized in source leaves and transported to fruit for supporting fruit growth in tree fruit species of the Rosaceae family. In apple (Malus domestica ), antisense suppression ofaldose-6-phosphate reductase, the key enzyme for sorbitol synthesis, significantly decreased the sorbitol concentration but increased the sucrose concentration in leaves, leading to a lower sorbitol but a higher sucrose supply to fruit in these plants. In response to this altered carbon supply, the transgenic fruit had lower concentration of sorbitol and much higher concentration of glucose but similar levels of fructose, sucrose, and starch throughout fruit development relative to the untransformed control. Activities of sorbitol dehydrogenase, fructokinase, and sucrose phosphate synthase were lower, whereas activities of neutral invertase, sucrose synthase, and hexokinase were higher in the transgenic fruit during fruit development. Transcript levels ofMdSOT1, MdSDHs, MdFK2, andMdSPS3/6 were downregulated, whereas transcript levels ofMdSUC1/4, MdSUSY1-3, MdNIV1/3, MdHK s, andMdTMT1 were upregulated in the transgenic fruit. These findings suggest that the Sucrose cycle and the sugar transport system are very effective in maintaining the level of fructose and provide insights into the roles of sorbitol and sucrose in regulating sugar metabolism and accumulation in sorbitol-synthesizing species. Apple fruit: The advantages of a flexible sugar cycle Analysis of the sugar metabolism and transport system in apple trees shows how the fruit fructose level and fruit production is largely maintained in response to decreased sorbitol synthesis in leaves. Disruption to developmental processes and environmental factors can alter the supply of sugars from leaves to fruit. Lailiang Cheng at Cornell University, New York, US, and co-workers examined sugar metabolism and transport in modified apple trees to ascertain how a deficiency in one sugar, sorbitol, influences fruit development and sugar accumulation. Ordinarily, fructose—the sugar that generates sweeter fruit—is mainly derived from sorbitol. The modified trees compensated for sorbitol loss by increasing their sucrose supply and converting the excess sucrose into fructose and glucose, largely sustaining fruit production and fructose level. The team's results demonstrate the metabolic flexibility of the sugar cycle in fleshy fruits.